RANCANG BANGUN DC TO DC BUCK CONVERTER DENGAN SISTEM KENDALI PI PADA NI ELVIS II DAN ANTARMUKA BERBASIS LABVIEW - Afaf Fadhil Rifai; Wahyudi Purnomo; Revirda Eka Putri (P3M Politeknik Negeri Indramayu, 2021)
Understanding basic concepts is an important thing in electronics, especially regarding the teaching aid of power electronic components. Given the need for students to study the model of electronic schematic with feedback controller, a media that can support this is needed. One of the developments in component technology and electronic circuits that can be studied is the DC voltage conversion, namely the DC to DC buck converter. This teaching aid model uses software, namely LabVIEW and the control and data acquisition hardware, namely NI ELVIS II. DC to DC buck converter schematic that can reduce the variable output voltage with a value range of 6 - 18VDC from an input voltage of 24VDC. PI feedback controller testing in the system experiment resulted in a difference of 0.1567% error using the PI controller parameter of Kp = 3.00 and Ti = 0.01. The test results with the PI controller show the expected response and can be applied to the buck converter circuit system. Testing the interface of the buck type DC to DC converter system is considered feasible as a learning aid with an overall interface quality value of 83.8% with student responds.